The consequence of matrix dysfunction on lung immunity and the microbiome in COPD. (27th June 2018) - Hussell, Tracy; Lui, Sylvia; Jagger, Christopher; Morgan, David; Brand, Oliver
The pulmonary extracellular matrix (ECM) is a complex network of proteins which primarily defines tissue architecture and regulates various biochemical and biophysical processes. It is a dynamic system comprising two main structures (the interstitial matrix and the basement membrane) which undergo continuous, yet highly regulated, remodelling. This remodelling process is essential for tissue homeostasis and uncontrolled regulation can lead to pathological states including chronic obstructive pulmonary disease (COPD). Altered expression of ECM proteins, as observed in COPD, can contribute to the degradation of alveolar walls and thickening of the small airways which can cause limitations in airflow. Modifications in ECM composition can also impact immune cell migration and retention in the lung with migrating cells becoming entrapped in the diseased airspaces. Furthermore, ECM changes affect the lung microbiome, aggravating and advancing disease progression. A dysbiosis in bacterial diversity can lead to infection, inducing epithelial injury and pro-inflammatory reactions. Here we review the changes noted in the different ECM components in COPD and discuss how an imbalance in microbial commensalism can impact disease development. A summary of the changes observed in the extracellular matrix and microbiome of the COPD lung http://ow.ly/Yj5730kuLbg